PERAN KUALITAS PRODUK DAN STRATEGI HARGA DALAM PEMBENTUKAN KEPUTUSAN KONSUMEN WARDAH [THE ROLE OF PRODUCT QUALITY AND PRICING STRATEGY IN SHAPING WARDAH CONSUMERS' PURCHASE DECISIONS] - Tajuddien, Rahadyan (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
This study aims to analyze the effects of product quality and price on purchasing decisions of Wardah Cosmetics consumers using Structural Equation Modeling (SEM) based on LISREL. The research employs a quantitative associative approach, with the population consisting of all Wardah Cosmetics consumers in South Tangerang City. A purposive sampling technique was applied, resulting in 98 respondents. Data were collected through a structured questionnaire measuring consumers’ perceptions of product quality, price, and purchasing decisions. Data analysis was conducted by testing the structural model to identify causal relationships among latent constructs. The results indicate that product quality has a positive and significant effect on purchasing decisions (β = 0.468; Z = 5.665; p 0.05), suggesting that better perceived product quality increases consumers’ purchasing decisions. Conversely, price has a negative and significant effect on purchasing decisions (β = −0.488; Z = −5.800; p 0.05), indicating that higher perceived prices tend to reduce purchasing decisions. Simultaneously, product quality and price explain 59.2% of the variance in purchasing decisions (R² = 0.592), while the remaining variance is influenced by other factors outside the research model. These findings highlight the importance of managing product quality and implementing appropriate pricing strategies to enhance consumers’ purchasing decisions. This study provides practical implications for Wardah Cosmetics management and contributes to the empirical literature on consumer behavior in the cosmetics industry.